Program Performance Analysis of Pekalongan.Nusantara Fishing Port - Much Arif Wijayanto; Agus Suherman; Abdul Kohar M. (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
The objective of this research is to find out the work program and performance percentage level of the Nusantara Fishery Harbor (NFH) of Pekalongan, using the Balanced Scorecard (BSC) analysis. The research method used in this research is the descriptive method and it is a case study research. The primary data are collected from interviews-, meanwhile, the secondary data are collected from the related services and literature study presented in the institutions having the connections to the observed objects. Data analysis uses the Balanced Scorecard (BSC) analysis. The research results show that the work program executed by the NFH of Pekalongan is almost the same in every year from 2007 to 2009, as many as 8 (eight) activities. Among them are, salary, allowance and wage management, responsible and continuous fish resource utilization program, office operation management, program development and financial administration program. fishery business development and management program, data development and fishery statistical program, fishery facility and infrastructure improvement and development program, and organization of revitalization program. Meanwhile, for performance level, the Nusantara Fishery Harbor of Pekalongan is excellent. This can be seen from the DOCS average value as much as 99.33%, in which, the 2007 DOCS value was 98.22% with the gap value of -1.75%, the 2008 DOCS value was 99.93% with the gap value of 0.07% and the 2009 DOCS value was 100% with the gap value of 0%. Key Words: Fishery Harbor, Performance Percentage